LAT1 acts as a crucial transporter of amino acids in human thymic carcinoma cells - Keitaro Hayashi; Promsuk Jutabha; Sumiko Maeda; Yothaisong Supak; Motoshi Ouchi; Hitoshi Endou; Tomoe Fujita; Masayuki Chida; Naohiko Anzai (Elsevier, 2016)
L-type amino acid transporter 1 (LAT1, SLC7A5) incorporates essential amino acids into cells. Recent studies have shown that LAT1 is a predominant transporter in various human cancers. However, the function of LAT1 in thymic carcinoma remains unknown. Here we demonstrate that LAT1 is a critical transporter for human thymic carcinoma cells. LAT1 was strongly expressed in human thymic carcinoma tissues. LAT1-specific inhibitor significantly suppressed leucine uptake and growth of Ty82 human thymic carcinoma cell lines, suggesting that thymic carcinoma takes advantage of LAT1 as a quality transporter and that LAT1-specific inhibitor might be clinically beneficial in therapy for thymic carcinoma.